Healing through Expression: How the Arts can be a Tool for Wellbeing and Empowerment for Syrian Refugees Youth in Jordan - Nashwan, Ayat; Steckler, Timothy; Abdulhaq, Bayan (Dirasat: Human and Social Sciences, 2019)
Humanitarian aidto refugees often focuses on immediate, practical issues,whether it involves food, water, medicine, shelter, or employment.But humanitarian aid workers and policymakers too often overlook issues involving refugees’ dignity, psychosocial wellbeing, and sense of purpose in a new country. For many, involvement in the arts can help refugees overcome these issues. This study posits the hypothesis that refugees perceive the arts as being beneficial to their wellbeing and empowerment. The study explores the perspectives of Syrian refugee youth in Jordan who are involved in the arts, focusing on dancers, visual artists, musicians, and actors through semi-structured interviews. The participants shared their thoughts, opinions, and stories in this process. The results of this study strongly indicates that the arts to positively impact refugees’ wellbeing in terms of connection to their culture and their mentality in Jordan, and to their empowerment by giving an added sense of purpose to their experience in Jordan.The evidence shows that the arts contribute significant psychosocial benefits, such as happiness, confidence, self worth, and mental health. Research further suggests that there exists a significant stigma attached to the arts that often hinders Syrian refugees’ ability to be involved in the arts. This study recommends that further steps be taken to incorporate the arts in refugees’ experiences, and to do more educational work to remove this stigma. The results of this study is expected to provide humanitarian workers including social workers and psychologists with more insight on how arts in general can be integrated in psychosocial intervention programs for Syrian refugees in Jordan.